Occurrence of emerging bisphenol S analogues in urine from five occupational populations in South China. (February 2023) - Pan, Yanan; Han, Liqiao; Chen, Xiang; Wei, Xin; Zhou, Xiaoyue; Liang, Dingshan; Yin, Renli; Jiao, Xiaoyang; Li, Huashou; Li, Adela Jing; Qiu, Rongliang
Graphical abstract: Abstract: Bisphenol S (BPS) and its 11 emerging analogues were investigated in 325 urine samples from five occupational populations in South China. Besides BPS, ten emerging BPS analogues were newly identified and detected in the urine. It should be noted that urinary concentrations of dominant BPS analogues of 2, 4′-bis(hydroxyphenyl)sulfone (2, 4-BPS), bis(3-allyl-4-hydroxyphenyl)sulfone (TGSA) and diphenylsulfone (DPS) were 1.1–2.3 times higher than that of BPS, with overall detection frequencies at 74–91 %. The median sum concentrations of the target 12 bisphenols (ng/mL) were found highest in urine from cashiers (1.12), followed by water plant staffs (0.994), teachers (0.552), doctors (0.408) and power plant staffs (0.333). The composition profile of the urinary dominant bisphenols was occupational-dependent, with 2, 4-BPS accounting for 45–73 % in cashiers and power plant staffs, and with DPS and TGSA for 74–82 % among doctors, teachers and water plant staffs. Significant correlations were found among the most frequently detected bisphenols in cashiers, indicating their common application and emission pathways. The median exposures based on estimated daily intakes (EDIs, ng/kg bw/day) for the 12 bisphenols in cashiers and water plant staffs (31.6–35.6) were 1.8–3.4 times higher than those of teachers, doctors and power plant staffs (10.6–17.5). This is the first study to identify multiple emerging BPS analogues in urine from occupational populations, especially cashiers and water plant staffs.